The Influence Of Financial Distress, Due Professional Care And Locus Of Control On Audit Quality In Accounting Firms In Bengkulu City In 2019-2022 - Riswandi, Pedi; Arnova , Iwin; Masdewa , Pheti (Journal of Management, Economic, and Accounting, 2024)
In the accounting business in Bengkulu City, the aim of this research is to determine what aspects influence audit quality, specifically looking at financial difficulties, professional care required, and locus of control. This study uses a quantitative research strategy based on questionnaires to collect primary data. All auditors employed by Bengkulu public accounting firms form the research population. A total of three KAPs from the city of Bengkulu will be registered in the Public Accounting Information System (SIKAP) in 2023. In this study, financial difficulties, locus of control, and appropriate professional care are the dependent variables. Fifteen auditors composed the sample for this study. According to the Findings, the following variables do not influence Following are some recommendations drawn from the research findings: audit quality: Financial Distress (p>0.05), Required Professional Care (p<0.026), and Locus of Control (p >0.277). This study found that audit quality was influenced simultaneously by Financial Distress, Due Professional Care, and Locus of Control, with a total effect size of 0.034<0.05.